Lithium‐Ion Batteries: Ultrathin [110]‐Confined Li4Ti5O12 Nanoflakes for High Rate Lithium Storage (Adv. Energy Mater. 22/2021). Issue 22 (10th June 2021) - Fu, Shuting; Yu, Xuefang; Wu, Qili; Yang, Xianfeng; Liu, Zheng; Li, Xiaohui; He, Shiman; Wang, Da; Li, Yanchun; Tong, Shengfu; Wu, Mingmei
Abstract : In article number 2003270, Shengfu Tong, Mingmei Wu and co‐workers design an oriented lithium titanate (Li4 Ti5 O12 ) anode for high‐rate lithium storage. [110]‐oriented channels in the structure enable ultrafast lithium ion transport. The lithium‐ion battery shows high rate capability and superior cycling stability. This [110]‐oriented Li4 Ti5 O12 material shows promise for application in high‐power energy storage facilities.